2020
DOI: 10.3390/computers9020024
|View full text |Cite
|
Sign up to set email alerts
|

Comparing Static and Dynamic Weighted Software Coupling Metrics

Abstract: Coupling metrics are an established way to measure software architecture quality with respect to modularity. Static coupling metrics are obtained from the source or compiled code of a program, while dynamic metrics use runtime data gathered e.g., by monitoring a system in production. We study weighted dynamic coupling that takes into account how often a connection is executed during a system's run. We investigate the correlation between dynamic weighted metrics and their static counterparts. We use data collec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 40 publications
(41 reference statements)
0
5
0
Order By: Relevance
“…Figure 1(a) compares classes before and after applying the SRP; the lack of cohesion is unrelated to SRP use, but the coupling relation decreases. The scale and granularity of the data demonstrate the value of coupling (Schnoor & Hasselbring, 2020) and cohesion metrics for large-scale industrial software systems.…”
Section: Introductionmentioning
confidence: 88%
“…Figure 1(a) compares classes before and after applying the SRP; the lack of cohesion is unrelated to SRP use, but the coupling relation decreases. The scale and granularity of the data demonstrate the value of coupling (Schnoor & Hasselbring, 2020) and cohesion metrics for large-scale industrial software systems.…”
Section: Introductionmentioning
confidence: 88%
“…a software system, which provides an established way to measure internal software quality concerning modularity [46]. The implemented Coupling metrics indicate loose coupling when the obtained values are low and a tight coupling when high [44].…”
Section: Available Metricsmentioning
confidence: 99%
“…Encapsulation refers to hiding internal details (e.g., attributes, internal implementation) to keep unrelated concerns isolated [46], and the application of encapsulation in scientific software has a direct effect on its performance [48]. Here, the number of private (or 'internal', as called in R) fields and methods are calculated by counting their occurrences in a module.…”
Section: Available Metricsmentioning
confidence: 99%
“…The authors demonstrated a relationship between the considered metrics and software security issues by using CWE/OWASP tools that were used for the classification of software vulnerabilities. In the same year, Schnoor and Hasselbring [7] conducted a study to find a relation between the dynamic weighted metrics and their corresponding static metrics. Their data were collected from four diverse experiments and the results showed that there was a strong relationship between dynamic and static metrics.…”
Section: Introductionmentioning
confidence: 99%